On the Distributional Implications of Demographic Change - Christian Geppert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper provides a quantitative assessment of the impact of future demographic change on the distributions of earnings and skills in the German economy. The model accommodates household heterogeneity along both, the intra- and the inter-generational dimension. The results suggest a decline in the skill premium of 30 percentage points until the year 2050 meanwhile, the college educated share of the population increases by about 4 percentage points. Welfare effects from changing wages, interests, and pensions are severe and amount to up to 6% of consumption in every period of the remaining lifetime. While welfare effects differ considerably across generations they are rather homogeneous across skill groups unless the educational choice of households is restricted.
Keywords: J11; I24; C68; 330